2021
DOI: 10.3390/ijerph182111190
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Role of Sociodemographic Factors in the Relationship between Physical Activity and Subjective Well-Being in Chilean Children and Adolescents

Abstract: Background: The relationship between physical activity habits and well-being is widely recognized; however, the interaction that these variables have with sociodemographic factors throughout life is only partially addressed in the literature, particularly in children and adolescents. The aim of this article is to analyze the moderating effect of sociodemographic factors and the possible interaction of these moderations in the relationship between physical activity and subjective well-being in children and adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…This study found that physical activity positively predicted subjective well-being, and the results obtained are consistent with previous research findings [ 39 ]. The positive effects of physical activity include better physical condition, positive psychological experiences, and harmonious interpersonal relationships.…”
Section: Discussionsupporting
confidence: 93%
“…This study found that physical activity positively predicted subjective well-being, and the results obtained are consistent with previous research findings [ 39 ]. The positive effects of physical activity include better physical condition, positive psychological experiences, and harmonious interpersonal relationships.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is largely in line with previous studies, which demonstrated that physical activity in general is associated with improved positive emotions and life satisfaction, and participation in organized physical activity in particular enhances subjective well-being in adolescents [ 18 , 58 ]. It follows that active participation in organized physical activity in school is a viable intervention strategy that can facilitate caring for adolescents’ mental health in southwest China [ 19 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Guidelines on Physical Activity and Sedentary Behavior issued by the World Health Organization (WHO) in 2020 recommended that adolescents should engage in moderate to vigorous physical activity for an average of 60 min (1 h) per day [ 17 ]. However, with the transition from childhood to adolescence, adolescents will gradually experience increased academic stress, more sedentary behavior, and decreased physical activity [ 18 , 19 ]. For example, the rate of physical inactivity among global school-aged adolescents is about 80%, and the proportion of adolescents with physical inactivity has gradually increased worldwide [ 20 ].…”
Section: Introductionmentioning
confidence: 99%